GE_GERICHTE C/9235/2016 vom 3. Juli 2018 - GE Cour de justice (2018)
ACTION EN CONTESTATION DE L'ÉTAT DE COLLOCATION ; DROIT D'ÊTRE ENTENDU ; CRÉANCE | CPC.152.al1; Cst.29.al2; LP.250.al1; LDIP.155.leti; CC.55; CO.718b; CO.719